2017
DOI: 10.1017/s1351324917000304
|View full text |Cite
|
Sign up to set email alerts
|

Lemaza: An Arabic why-question answering system

Abstract: Question answering systems retrieve information from documents in response to queries. Most of the questions arewho-andwhat-type questions that deal with named entities. A less common and more challenging question to deal with is thewhy-question. In this paper, we introduceLemaza(Arabic forwhy), a system for automatically answeringwhy-questions for Arabic texts. The system is composed of four main components that make use of the Rhetorical Structure Theory. To evaluateLemaza, we prepared a set ofwhy-question–a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…The results showed that the RST-based method outperformed the baseline method. The same authors [83] experimented with their RST-based method by using 110 "why" questions on the same dataset. The test was to evaluate the performance of the RST-based method when one of the NLP techniques of the first and second components was skipped each time.…”
Section: Proposed Qa Systems For Arabic Nonfactoid Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that the RST-based method outperformed the baseline method. The same authors [83] experimented with their RST-based method by using 110 "why" questions on the same dataset. The test was to evaluate the performance of the RST-based method when one of the NLP techniques of the first and second components was skipped each time.…”
Section: Proposed Qa Systems For Arabic Nonfactoid Questionsmentioning
confidence: 99%
“…Content may change prior to final publication. [83] and FastQA [84]. These models can be used in the answer extraction component of QA systems.…”
Section: Proposed Qa Systems For Arabic Nonfactoid Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…LEMAZA (Azmi et al, 2017) is an open-domain Arabic Question Answering system concerned with answering questions of the type "why". After the Question Analysis, and the text Document Preprocessing, phases, the most related passages to the question are extracted and verified in the Document|Passage Retrieval phase using Lemur retrieval engine.…”
Section: Related Workmentioning
confidence: 99%
“…The components of Question Answering systems differ according to their purpose. Some systems specialize in answering questions asked within a specific domain (such as Islamic questions) (Abdi et al, 2020), and some are concerned with answering questions of a specific type ("why", "when",…) (Azmi et al, 2017). Other systems, called open-domains Question Answering systems, try to answer many types of questions and within different domains, and they are the most general systems (AL-SMADI et al, 2017; Zhou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%